Atomistic Simulation of Atomic Force Microscopy Imaging of Hydration Layers on Calcite, Dolomite, and Magnesite Surfaces - Reischl, Bernhard; Raiteri, Paolo; Gale, Julian; Rohl, Andrew (AMER CHEMICAL SOC, 2019)
© 2019 American Chemical Society. Advances in atomic force microscopy (AFM) in water have enabled the study of hydration layer structures on crystal surfaces, and in a recent study on dolomite (CaMg(CO3)2), chemical sensitivity was demonstrated by observing significant differences in force-distance curves over the calcium and magnesium ions in the surface. Here, we present atomistic molecular dynamics simulations of a hydration layer structure and dynamics on the (101 4) surfaces of dolomite, calcite (CaCO3), and magnesite (MgCO3), as well as simulations of AFM imaging on these three surfaces with a model silica tip. Our results confirm that it should be possible to distinguish between water molecules coordinating the calcium and magnesium ions in dolomite, and the details gleaned from the atomistic simulations enable us to clarify the underlying imaging mechanism in the AFM experiments.